MPEG-4 and H.263 video traces for network performance evaluation. - Fitzek, F.H.P (IEEE Network : the magazine of global information exchange)
MPEG-4 and H.263 encoded video is expected to account for a large portion of the traffic in future wireline and wireless networks. However, due to a lack of sufficiently long frame size traces of MPEG-4 and H.263 encoded videos, most network performance evaluations currently use MPEG-1 encodings. We present and study a publicly available library of frame size traces of long MPEG-4 and H.263 encoded videos, which we have generated at the Technical University Berlin. The frame size traces have been generated from MPEG-4 and H.263 encodings of over 10 video sequences each 60 minutes long. We conduct a thorough statistical analysis of the traces